THE HISTORIOGRAPHY OF THE ACTIVITIES OF THE JUSTICE BODIES OF THE TURKESTAN ASSR: TYPES AND ANALYSIS - Ulugbek Olimovich Juraboyev (PEDAGOGS, 2025)
Annotation: This article provides an analysis of sources studying the justice system and its activities in the Turkestan ASSR. Information is provided on scientific literature, archival sources, statistical collections, and periodical press sources related to the development of the organization and activities of justice bodies.